2017
DOI: 10.15407/ubj89.05.062
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of LPS-induced ROS production and NF-?B nuclear translocation by N-stearoylethanolamine in macrophages

Abstract: N-Stearoylethanolamine (NSe) is a minor lipid that belongs to the N-acylethanolamines family that K e y w o r d s: N-stearoylethanolamine, reactive oxygen species, translocation of NF-κB in macrophages inrat, lPS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…But in our study, we have shown that the activation of NF-κB by LPS-induced TLR4/MyD88-accelerated ROS production is collectively LC8 and IkB-a dependent. Some reports, utilizing LPS as a ROS inducer, support our results ( 74 , 75 ). The results of our study with a little modification from those of Cario ( 76 ) and Fukata et al.…”
Section: Discussionsupporting
confidence: 90%
“…But in our study, we have shown that the activation of NF-κB by LPS-induced TLR4/MyD88-accelerated ROS production is collectively LC8 and IkB-a dependent. Some reports, utilizing LPS as a ROS inducer, support our results ( 74 , 75 ). The results of our study with a little modification from those of Cario ( 76 ) and Fukata et al.…”
Section: Discussionsupporting
confidence: 90%
“…It has been known that NAEs, particularly NSE, exhibit adaptogenic, membrane-protective, antioxidant, immunomodulatory, anti-inflammatory, anti-allergic and anti-toxic effects [36]. Additionally, NSE modulated nitric oxide level (by affecting activi ty of constitutive and inducible NO synthases under different pathological conditions) [37] and reactive oxygen species level (by reducing the production of superoxide anion under LPS treatment) [38]. It worth to mentioning that effect of NSE is observed only under pathological conditions and does not show up under healthy normal conditions [39,40].…”
Section: Total Level Of Phospholipids and Level Of Individual Phosphomentioning
confidence: 99%
“…Previously, on the different models of pathological conditions we have shown that NSE decreased the production and content of in ammatory cytokines (IL-1β, TNF-α) [15]. Further studies reported that particular NSE effect was associated with the inhibition of nuclear NF-κB translocation in LPS-activated rat peritoneal macrophages [ 23 ]. It is known that LPS-induced in ammatory response could be inhibited by the activation of either PPAR-γ or LXRα [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 93%